Improved in Vitro Folding of the Y2 G Protein-Coupled Receptor into Bicelles - Schmidt, Peter; Bender, Brian J.; Kaiser, Anette; Gulati, Khushboo; Scheidt, Holger A.; Hamm, Heidi E.; Meiler, Jens; Beck-Sickinger, Annette G.; Huster, Daniel (Frontiers in Molecular Biosciences, 2018)
Prerequisite for structural studies on G protein-coupled receptors is the preparation of highly concentrated, stable, and biologically active receptor samples in milligram amounts of protein. Here, we present an improved protocol for E. coli expression, functional refolding and reconstitution into bicelles of the human neuropeptide Y receptor type 2 (Y2R) for solution and solid-state NMR experiments. The isotopically labeled receptor is expressed in inclusion bodies and purified using SDS. We studied the details of an improved preparation protocol including the in vitro folding of the receptor, e.g. the native disulfide bridge formation, the exchange of the denaturating detergent SDS, and the functional reconstitution into bicelle environments of varying size. Full pharmacological functionality of the Y2R preparation was shown by a ligand affinity of 4 nM and G-protein activation. Further, simple NMR experiments are used to test sample quality in high micromolar concentration.